PENGARUH KONSENTRASI ASAM SITRAT DAN SUHU PENGERINGAN TERHADAP KARAKTERISTIK FISIK, KIMIA DAN SENSORIS MANISAN KERING LABU SIAM (Sechium edule Sw.) DENGAN PEMANFAATAN PEWARNA ALAMI DARI EKSTRAK ROSELA UNGU (Hibiscus sabdariffa L.) - Fajarwati, Nur Hajriyani; Parnanto, Nur Her Riyadi; Manuhara, Godras Jati (Universitas Sebelas Maret (UNS), 2017)
The aim of this research is to know the effect of citric acid concentration on the characteristics of physical (texture, color), chemical (pH, water content, total anthocyanin and antioxidant activity) and sensory (color, flavor, texture, aroma, overall) and the effect of drying temperature to the physical characteristics (texture, color), chemical (pH, water content, total anthocyanin and antioxidant activity) and sensory (color, flavor, texture, aroma and overall) as well as knowing the most preferred formulation. The research design used completely randomized design with two factors, the concentration of citric acid (1.5%; 2%; 2.5%) and the drying temperature (50oC, 60oC, 70oC). The data were then analyzed using ANOVA. If there is a difference, the followed by DMRT at 5% significance level. The results showed that the concentration of citric acid and drying temperature affect on physical characteristics (texture, color), chemical characteristics (pH, water content, total anthocyanins, antioxidant activity) and sensory characteristics. The best dried candied chayote based on the sensory characteristics is candied with 1.5% citric acid concentration and drying temperature 60°C with the value of hardness (338.47 N), L (lightness) (36.41), a (redness) (7.63), b (yellowness) (1.22), pH (3.16), water content (13.33%), total anthocyanins (299.74 mg / L) and antioxidant activity (11.64%).